การสะสมกลิ่นไม่พึงประสงค์ในน้ำและดินพื้นท้องน้ำของกว๊านพะเยา จังหวัดพะเยา: Accumulation of off-flavor in water and bottom soil of Kwan Phayao, Phayao province - Kannika, Korntip; Whangchai, Niwooti; Nuangmek, Wipornpan; Pitukpol, Santiwat (Asian Health, Science and Technology Reports, 2011)
The aim of this study was detected of accumulation of off-flavor in water and bottom soil of Kwan Phayao, Phayao Province. Water and bottom soils sampling 7 stations were collected 1 time/month. Field survey was 8 months between January-August 2010. Off-flavor compound; geosmin (GSM) and MIB (2-methylisoborneol: MIB) in water and bottom soil was examined using Solid Phase Microextraction (SPME) and Gas Chromatography Mass Spectrometry (GC/MS). The result showed that water quality in Kwan Phayao indicated that the standard for surface water quality Class 2. Accumulation of off-flavor in water and soid bottom showed geosmin and MIB in Station KP1 Ing River (inside) gave the highest content. Geosmin content in water and bottom soil was 11.8 13.8 ug/L. and 6.0 6.8 ug/kg., respectively. MIB content in water and bottom soil were 8.0 6.3 ug/L. and 7.0 5.2 ug/kg., respectively. The accumulation of off-flavor in water and soid bottom in Kwan Phayao showed a positive correlation of actinomycetes and geosmin and MIB in water and soid bottom in Kwan Phayao. This study implied that the accumulation of off-flavor compound; geosmin and MIB in water and bottom soil correlated strongly with increasing amount of actinomycetes in bottom soil.